Peran Program Desa Mandiri Pangan dalam Mendukung Ketahanan Pangan Rumah Tangga (Studi Kasus di Desa Panjampang Bahagia Kecamatan Simpur Kabupaten Hulu Sungai Selatan) - Bayu Kurniawan; Mariani Mariani; Taufik Hidayat (AGRIDES: Jurnal Agribisnis Perdesaan, 2014)
The development of Village Food Resilience Program (DMP), in order to integrate many community food security empowerment programs , requires community participation. It is expected that by this approach all villages capable in achieving food security independently. The study aimed: (1) to explore the role of DMP program in supporting household food security; and (2) to recognize the problem encountered on the DMP program. The survey method is practiced in the study where is 33 respondents were taken as samples. The population is the members of affi nity groups who receive two programs, which are: credit facility program and poultry business improvement program. The study revealed that the DMP program is very important to support household foo d security in the study site. Even though there are many problems to settl e. The infrastructures and human resources are limited to support food security prog rams. Several members of affi nity group are not forward-thinking and less-discipline in returning the credit. In addition, the credit fund also limited and cannot meet the increasing credit demand.